Anhedonia and individual differences in orbitofrontal cortex sulcogyral morphology. Issue 11 (6th October 2016) - Zhang, Hyden; Harris, Lauren; Split, Molly; Troiani, Vanessa; Olson, Ingrid R.
Abstract: Three types of orbitofrontal cortex (OFC) sulcogyral patterns that have been identified in the population, and the distribution of these three types in clinically diagnosed schizophrenic patients has been found to be distinct from the normal population. Schizophrenia is associated with increased levels of social and physical anhedonia. In this study, we asked whether variation in anhedonia in a neurologically normal population is associated with altered sulcogyral pattern frequency. OFC sulcogyral type was classified and anhedonia was measured in 58 normal young adults, and the relationship between OFC sulcogyral type and anhedonia was explored. In line with other studies conducted in chronic schizophrenia, individuals with higher levels of physical anhedonia demonstrated atypical sulcogyral patterns. Individuals with higher physical anhedonia showed a reduced incidence of Type I OFC and an increased incidence of Type II OFC in the left hemisphere compared to individuals with lower physical anhedonia. These findings support the notion that Type I OFC sulcogyral pattern is protective of anhedonia compared to Type II, even in individuals that are not schizophrenic. Overall, these results support the view that symptoms and neural indices typically associated with neuropsychiatric disorders actually reflect quantitative traits that are continuously distributed throughout the general population. Hum Brain Mapp 37:3873–3881, 2016 . ©2016 Wiley Periodicals, Inc .